Ergonomics: a study of influence on productivity (REGE Revista de Gestão, 2009)
Companies, governments and society are showing an increasing interest in ergonomics as applied to productive activities. Therefore the Brazilian government has issued Norma Regulamentadora 17 - Ergonomia to establish parameters for adapting working conditions to the psycho-physiologic characteristics of workers. This work evaluated ergonomics, productivity and work stations at “Magnifica Confecções” in Paranaíba, where most machines are operated in a seated position with repetitive movements. Therefore ergonomic concepts aspects are decisive to improve productivity and well-being of collaborators. Ergonomics is used at the work stations in a constructive and participative problem solving process requiring understanding of the tasks, activities, problems and performance demanded. For this reason, resultant data was supported by questionnaires answered by the diverse participants that developed these activities resolving these problems.